Research participants' skills development as HIV prevention peer educators in their communities. (September 2018) - Morar, Neetha Shagan; Naidoo, Sarita; Goolam, Ahmed; Ramjee, Gita
This article describes the influence of a peer education programme on skills development among 22 women participating in HIV prevention trials. Interviews were used to collect data on peer educator experiences and their opinions of the trainings. The training enhanced their agency and confidence to engage their family and community on health promotion, including HIV prevention research procedures, thus improving their self-esteem and communication skills. Training and partnering with clinical trial participants as peer educators is an effective and sustainable community-based approach for HIV prevention.